Environment and Embodiment in Early Modern England - Sullivan, Jr, Garrett A. author. aut Link
XII, 213 p.
Keywords: Eleven essays invite us to rethink not only what constitutes an environment but also where the environment ends and selfhood begins. The essays examine the dynamic and varied mediations early modern writers posited between microcosm and macrocosm, ranging from discourses on the ecology of passions to striking examples of distributed cognition.